MEMPERTAHANKAN TUJUAN PERATURAN DAFTAR NEGATIF INVESTASI DALAM MENGENDALIKAN DOMINASI KEPEMILIKAN ASING (STUDI KASUS PADA INDUSTRI TELEKOMUNIKASI) - Sulistyowati Sulistyowati; Paripurna Paripurna (Jurnal Dinamika Hukum, 2014)
Indonesia’s Investment Law and Negative Investment List (DNI) are not applicable to capital market transactions. Interpreted literally, this means foreign investors can arbitrarily increase their share participation in a company by engaging capital market transactions. This is not acceptable since the government puts a limit on foreign shares participation in certain business sectors. This normative-empiric study discusses practices in telecommunication industry that deviate from DNI, the conse-quences, and viable solutions. We found that literal interpretation is inconsistent to the objective of the DNI. We offer alternative approach that is more applicable and suitable to the given objec-tives.Keywords    :    negative investment list, foreign ownership restriction, portfolio investment, capital market transaction.